"Frustration" in the Court of Appeal - McLauchlan, David W (Victoria University of Wellington Law Review, 2013)
This article discusses the decision of the New Zealand Court of Appeal in Planet Kids Ltd v Auckland Council [2012] NZCA 562, [2013] 1 NZLR 485. The Court upheld the Council's argument that its contract with the appellants had been frustrated, and therefore it was released from the obligation to render the performance it had promised, notwithstanding that it had achieved in substance everything that it set out to achieve at the time of the contract. The author argues that the case was wrongly decided.